Efektivitas Program Sosial Bank Indonesia Jawa Barat dalam Meningkatkan Kesejahteraan Anggota Kelompok Tani Agronative - Valeri, Eirene; Setiawan, Iwan; Wulandari, Eliana; Syamsiyah, Nur (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The Bank Indonesia Social Program is here to carry out community development, one of its targets is Agronative. The aim of the research is to describe the characteristics of farmers in implementing PSBI, determine the impact of development on the welfare of farming communities, and determine the effectiveness of implementing PSBI in Agronative. The research method uses quantitative methods with an explanatory survey. 28 samples were taken using a saturated sample census. The author uses descriptive analysis and simple regression as data analysis techniques. The results of the research show that most of the farmers are aged 36-45 years, have 3 family members, with primary school education, have 10 years of farming experience where the source of information comes from relatives, manage 2,250 m² of land with land tenant status with a middle income . The R2value obtained is 0.185, meaning that the influence of PSBI on farmer welfare can be explained by the community development variable of 18.5%. Even though there is still a shortage of human resources, this program has been effective in improving the welfare of its members.